Analysis of Various Carriers Overlapping PWM Strategies for a Single Phase Ternary Multilevel Inverter - C. R. Balamurugan; R. Bensraj (International Journal of Applied Power Engineering (IJAPE), 2018)
Multilevel inverters are used in power conversion system due to improved voltage and current waveforms. This paper presents the comparison of various Carrier Overlapping Pulse Width Modulation (COPWM) Strategies for the three phase Cascaded Multi Level Inverter (CMLI). Various new schemes adopting the constant switching frequency and also variable switching frequency multicarrier control freedom degree combination concepts are developed and simulated for the chosen three phase CMLI. A single phase CMLI is controlled in this paper with Sinusoidal PWM (SPWM) reference along with Carrier Overlapping (CO) techniques and simulation is performed using MATLAB-SIMULINK. The variation of fundamental RMS output voltage and total harmonic distortion is observed for various carrier overlapping techniques. Among the various equal amplitude and unequal amplitude carriers carrier overlapping techniques such as COPWM-A, COPWM-B and COPWM-C, It is observed from Table 4 that all PWM method provides output with relative low distortion for equal amplitude carriers. If equal voltage sources are chosen then the THD will be less in the case of unequal amplitude carriers. But for the unequal voltage sources the THD is more in the case of unequal amplitude carriers.  It is observed from simulation results that (Table-5) almost in all the strategies unequal amplitude carriers gives more fundamental RMS values compared to equal amplitude carriers. It is seen from table 6 that peak voltage is more in the case of unequal amplitude carriers compared to equal amplitude carriers. It is observed from the table 7 that dc components are less in both equal and unequal amplitude carriers.